Improving Students' Speaking Ability using Virtual Role Play during Pandemic COVID-19 at 117 Junior High School Jakarta - Boy Handrison; Roslaini Roslaini (UICELL, 2022)
This research was aimed at improving students’ speaking ability using virtual role play. It was a virtual classroom action research conducted at 117 Junior High School Jakarta. The respondents of the research were 36 seventh grade students. The data were collected by using observation and giving speaking test. The learning syntax was designed for three stages, namely preparation, implementation, and reflection. The learning process related with preparing learning, organizing dialog scripts, giving the scripts to the students by WhatsApp, practicing the dialog, and assessing learning outcomes. To get the data of the research, the writer implemented virtual classroom action research for three cycles. In the first cycle, the students were practicing short dialogue scripts, and for the second cycle the students were given dialogue scripts in form of drama. Then, at the last cycle, the students were making and practicing their own dialog scripts. After conducting the research, the result showed that in the first cycle, the active students were 58% in which the average score is 68. In the second cycle, the active students were 74.%, and the average score is 75. In the last cycle the active students become 86.%, and the average score is 82. Finally, it could be concluded that by using virtual role play the active students were increasing during pandemic, and the students were able to create and practice new dialogs. Keywords: CAR, Virtual Role Play, Speaking Ability